Complex Physiological Response of Norway Spruce to Atmospheric Pollution – Decreased Carbon Isotope Discrimination and Unchanged Tree Biomass Increment - Čada, Vojtěch; Šantrůčková, Hana; Šantrůček, Jiří; Kubištová, Lenka; Seedre, Meelis; Svoboda, Miroslav (Frontiers in Plant Science, 2016)
Atmospheric pollution critically affects forest ecosystems around the world by directly impacting the assimilation apparatus of trees and indirectly by altering soil conditions, which subsequently also leads to changes in carbon cycling. To evaluate the extent of the physiological effect of moderate level sulfate and reactive nitrogen acidic deposition, we performed a retrospective dendrochronological analysis of several physiological parameters derived from periodic measurements of carbon stable isotope composition (13C discrimination, intercellular CO2 concentration and intrinsic water use efficiency) and annual diameter increments (tree biomass increment, its inter-annual variability and correlation with temperature, cloud cover, precipitation and Palmer drought severity index). The analysis was performed in two mountain Norway spruce (Picea abies) stands of the Bohemian Forest (Czech Republic, central Europe), where moderate levels of pollution peaked in the 1970s and 1980s and no evident impact on tree growth or link to mortality has been reported. The significant influence of pollution on trees was expressed most sensitively by a 1.88‰ reduction of carbon isotope discrimination (∆13C). The effects of atmospheric pollution interacted with increasing atmospheric CO2 concentration and temperature. As a result, we observed no change in intercellular CO2 concentrations (Ci), an abrupt increase in water use efficiency (iWUE) and no change in biomass increment, which could also partly result from changes in carbon partitioning (e.g. from below- to above-ground). The biomass increment was significantly related to ∆13C on an individual tree level, but the relationship was lost during the pollution period. We suggest that this was caused by a shift from the dominant influence of the photosynthetic rate to stomatal conductance on ∆13C during the pollution period. Using biomass increment-climate correlation analyses, we did not identify any clear pollution-related change in water stress or photosynthetic limitation (since biomass increment did not become more sensitive to drought/precipitation or temperature/cloud cover respectively). Therefore, we conclude that the direct effect of moderate pollution on stomatal conductance was likely the main driver of the observed physiological changes. This mechanism probably caused weakening of the spruce trees and increased sensitivity to other stressors.